Hell's corner [large type] - Baldacci, David (Baldacci, David. Camel Club., 2010)
A bomb detonates in the White House immediately after the British Prime Minister departs from the State Dinner. Oliver Stone, who witnesses the event, believes the Prime Minister and the President were the targets of a terrorist plot. MI-5 agent Mary Chapman is assigned to assist the Stone and his Camel Club with the investigation, which reveals that the bombing may have actually been botched and is part of a darker, deadlier conspiracy.